Islamic Character Education for Early Childhood in the Digital Era: An Integrated Ecological Model - Supriyani Supriyani; Siti Aisyah; Siti Kholijah; Haris Riyadi; Samuel Karim (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2026)
Early childhood is the most formative period for character development, yet the rapid proliferation of digital devices poses serious challenges to instilling Islamic values. Children are increasingly exposed to inappropriate content, gadget addiction, and diminished religious habituation due to insufficient adult guidance. This library research synthesizes 30 Indonesian scientific journal articles published between 2016 and 2024 to examine the concepts, challenges, strategies, and conceptual models of Islamic character education for early childhood in the digital era. The findings reveal four main themes: Islamic character education is a process of embedding morality, religious values, and praiseworthy behaviors from an early age through modeling, habituation, and storytelling; the digital era introduces risks such as overexposure to gadgets, non-educational content, and reduced face-to-face social interaction; effective strategies include parental and teacher modeling, consistent habituation, selective use of Islamic digital content, and close collaboration between families and early childhood education institutions. An ecological model comprising four interconnected layers—core Islamic values (aqidah, ibadah, akhlak), value-instillation methods (exemplary conduct, habituation, advice), educational environments (family, teachers, PAUD institutions, community), and digital literacy (content selection, screen time limits, active mentoring)—is proposed. This integrated model offers a balanced approach to protecting children from digital risks while harnessing technology as a positive medium for Islamic value transmission. The study contributes a novel synthesis that bridges Islamic pedagogy, early childhood development, and digital era challenges.